Cushing's syndrome secondary to adulterated complementary and alternative medicine. - Shariff Ghazali, Sazlina; Ahmad, Zaiton (Academy of Family Physicians of Malaysia, 2009)
This is a case of a 65 year old lady who presented with Cushing's syndrome secondary to ingestion of a complementary and alternative medicine that has been adulterated with exogenous glucocorticoids. In a clinical consultation, it is important to include assessment of complementary and alternative medicine use for a comprehensive care.